2022
DOI: 10.1186/s12889-022-12882-x
|View full text |Cite
|
Sign up to set email alerts
|

Covert use of reversible contraceptive methods and its association with husband’s egalitarian gender attitude in India

Abstract: Background In a patriarchal society, women often keep their use of contraceptives secret in order to meet their reproductive goals and satisfy their reproductive preferences. Nevertheless, to our knowledge, women’s covert contraceptive use and its association with husband’s gender attitude have not been studied in the Indian settings. The present study estimates the extent of covert modern contraceptive use (CCU) among women and its linkage with husbands’ gender attitudes in India. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…This finding regarding wives' relatively greater education is especially interesting in conjunction with our finding that wives’ greater absolute level of education is associated with decreased odds of covert contraceptive use. A similar pattern was found in a recent study in India, though not reaching statistical significance in that study (Vishwakarma and Shekhar 2022). Overall, we can speculate from these results that wives’ absolute education may be associated with empowerment to openly use contraception, while having an educational advantage relative to husbands may be associated with greater incentive to implement preferences covertly.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding regarding wives' relatively greater education is especially interesting in conjunction with our finding that wives’ greater absolute level of education is associated with decreased odds of covert contraceptive use. A similar pattern was found in a recent study in India, though not reaching statistical significance in that study (Vishwakarma and Shekhar 2022). Overall, we can speculate from these results that wives’ absolute education may be associated with empowerment to openly use contraception, while having an educational advantage relative to husbands may be associated with greater incentive to implement preferences covertly.…”
Section: Discussionsupporting
confidence: 91%
“…More generally, the promotion of egalitarian gender ideals among women and men may contribute to greater concordance both by empowering women and by lowering the likelihood of relationship stress sometimes associated with women having an educational advantage. This approach is supported by Vishwakarma and Shekhar (2022) who found that there is less covert use of contraception in households where the husband holds more egalitarian gender attitudes.…”
Section: Discussionmentioning
confidence: 90%
“…There is a high likelihood that this group of women was using contraceptives without the knowledge of their partners. As evident in previous studies [36][37][38], women may decide to covertly use contraception due to the inability to have a fruitful discussion with partners or partners' disapproval of the method used. There are also cases where attempts to negotiate safer sex have led to incidences of spousal violence [6].…”
Section: Discussionmentioning
confidence: 95%
“…This is because the discovery of covert use of contraceptives by an unsupportive partner may lead to marital disharmony and sometimes violence which does not in any way promote the institution of marriage. Since male disapproval is reported to be one of the main causes of the covert use of contraceptives by women [36][37][38], it is thus important that family planning managers in the country should give more relevance to more couple-oriented approaches to improving access to family planning services for married men and women in the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation